ANALISIS PENGARUH AUDIT TENURE, UKURAN KAP DAN DIVERSIFIKASI GEOGRAFIS TERHADAP MANAJEMEN LABA - Vina Kholisa Dinuka; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2014)
This study aims to examine the influence of audit tenure, audit firm size and geographic diversification towards earnings management in manufacturing compnies. Audit tenure is measured by the amount of the year of work relationship between auditee and the last public accountant firm. Audit firm size is measured by dummy variabel. The Audit firm is divided into audit firms that affiliated with big four and non big four audit firms. And geographic diversification is measured by the number of firms geographic segments.The population of this study are the manufacturing companies that listed in Indonesia Stock Exchange (BEI) in 2012. Purposive sampling is used for sampling method. And multiple regression technique is used for the data analysis. The total number of samples for this study are 94 companies. But, there are found 16 samples as outlier should be excluded from sample observation. So, the final samples for this study are 78 companies.The result of this study indicates that audit tenure have positif significant influence in earnings management, audit firm size have negative significant influence in earnings management. Meanwhile, geographic diversification don’t have significant influence to earnings management.